ABOUT THE ETERNAL ENGINE (Academicia Globe: Inderscience Research, 2024)
First of all, we need to understand that a perpetual motion machine is not just a perpetual motion machine, just like the planets and stars are in perpetual motion. The so-called perpetual motion machine is a device that not only moves indefinitely, but also produces useful work, and the energy transferred to this device is greater than the amount of energy that is extracted from it.